\(\displaystyle{7}{x}_{{1}}+{3}{x}_{{2}}={6}\)

\(\displaystyle-{6}{x}_{{1}}-{3}{x}_{{2}}={4}\)

Ax=B

\(\displaystyle\Rightarrow{x}={A}^{{-{1}}}{B}\)

Here \[A=\begin{bmatrix}7&3\\-6&-3\end{bmatrix}B=\begin{bmatrix}6\\4\end{bmatrix}\]

\[x=A^{-1}B=\begin{bmatrix}1&1\\-2&-\frac{7}{3}\end{bmatrix}\begin{bmatrix}6\\4\end{bmatrix}\]

\(\displaystyle{7}{x}_{{1}}+{3}{x}_{{2}}={6}\)

\(\displaystyle-{6}{x}_{{1}}-{3}{x}_{{2}}={4}\)

\(\displaystyle{A}{x}={B}\)

\(\displaystyle\Rightarrow{x}={A}^{{-{1}}}{B}\)

Here \[A=\begin{bmatrix}7&3\\-6&-3\end{bmatrix}B=\begin{bmatrix}6\\4\end{bmatrix}\]

\[=\begin{bmatrix}1&1\\-2&-\frac{7}{3}\end{bmatrix}\begin{bmatrix}6\\4\end{bmatrix}\]

\[=\begin{bmatrix}6+4\\-12-\frac{28}{3}\end{bmatrix}\]

\[=\begin{bmatrix}10\\-64/3\end{bmatrix}\]